Fabrication of ceramic microneedles – The role of specific interactions between processing additives and the surface of oxide particles in Epoxy Gel Casting. Issue 16 (December 2016) - Olhero, S.M.; Lopes, E.; Ferreira, J.M.F.
Abstract: Epoxy Gel Casting (EGC) was recently coined to designate a setting mechanism based on the in situ polymerization of epoxy resins dissolved in the aqueous dispersion media of ceramic powder suspensions upon adding suitable amine-based crosslinking agents. The specific interactions between the surface of the powder particles and the processing additives are likely to determine different partitions of the crosslinking species, dissolved in the bulk solution, or adsorbed at the surface of the particles, and affect the EGC process. The present work aims at evaluating the influence of surface chemistry on the extent of the specific interactions at the solid/liquid interface and how it affects the polymerization kinetics and the properties of ceramic green bodies consolidated by EGC. Three different ceramic oxides (alumina, zirconia and fused silica) having similar particle size distributions were used. Stable colloidal suspensions with 45 vol.% solids were prepared by dispersing the powders in aqueous solutions containing a fixed amount of a common dispersant and various dissolved amounts of an epoxy resin. Zeta potential, rheological measurements and calorimetry were used to assess the specific interactions and their effects on the consolidation kinetics upon adding a polyamine hardener, and on the final properties of consolidated parts. With the isoelectric point of the naked particle surface decreasing, there were noticeable decreases in gelation time, shrinkage, green density, and flexural strength of the green ceramic body's properties. An interaction model is proposed to explain the observed differences. The potential of EGC to consolidate ceramic microneedles cast in soft rubber moulds was demonstrated.